(untitled) (Scientific journal of the Fergana State University, 2023)
In order to increase the fire resistance of polyacrylonitrile fabric, it was originally modified with urea. The modified polyacrylonitrile fabric was then chemically treated with orthophosphate acid, resulting in the synthesis of a flammable PAN fabric. The composition and combustion rate of the refractory polyacrylonitrile material containing the synthesized N and P were studied using Fourier infrared spectroscopy, X-ray phase analysis, and limited oxygen index. The limited oxygen index value of fire-resistant polyacrylonitrile fabric was 28.5% after 20 wash cycles, which indicates its washing resistance and fire resistance.